2018
DOI: 10.1038/s41598-018-24688-2
|View full text |Cite
|
Sign up to set email alerts
|

Self-homodimerization of an actinoporin by disulfide bridging reveals implications for their structure and pore formation

Abstract: The Trp111 to Cys mutant of sticholysin I, an actinoporin from Stichodactyla helianthus sea anemone, forms a homodimer via a disulfide bridge. The purified dimer is 193 times less hemolytic than the monomer. Ultracentrifugation, dynamic light scattering and size-exclusion chromatography demonstrate that monomers and dimers are the only independent oligomeric states encountered. Indeed, circular dichroism and fluorescence spectroscopies showed that Trp/Tyr residues participate in homodimerization and that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 104 publications
0
2
0
Order By: Relevance
“…To test this hypothesis, we structurally designed a disulfide-stabilized dimer of CelTOS through incorporation of site-targeted cysteine substitutions. Valle et al used a similar disulfide bridge approach to lock sticholysin I in the homo-dimer state (Valle et al, 2018). The disulfide locked sticholysin I homo-dimer could not form pores and was 193 times less hemolytic than the WT protein (Valle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To test this hypothesis, we structurally designed a disulfide-stabilized dimer of CelTOS through incorporation of site-targeted cysteine substitutions. Valle et al used a similar disulfide bridge approach to lock sticholysin I in the homo-dimer state (Valle et al, 2018). The disulfide locked sticholysin I homo-dimer could not form pores and was 193 times less hemolytic than the WT protein (Valle et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Valle et al used a similar disulfide bridge approach to lock sticholysin I in the homo-dimer state (Valle et al, 2018). The disulfide locked sticholysin I homo-dimer could not form pores and was 193 times less hemolytic than the WT protein (Valle et al, 2018). Similarly, Nguyen et al created double-cysteine LukF (Leukocidin fast fraction) mutants and showed the disulfide-trapped mutants were inactive due to the transition arrest from pre-pore to pore (Nguyen, Higuchi, & Kamio, 2002).…”
Section: Discussionmentioning
confidence: 99%